Predicting homebuyers’ intentions of inhabiting eco-friendly homes: The case of a developing country - Tan, Teck-Hong * (2012)
Malaysian housing developers are still weighing the costs and benefits of building environmentally sensitive homes as many of them are concerned that there is not enough demand for these homes. The objective of this paper is to examine the relative importance of psychosocial, housing and demographic determinants in influencing intention to inhabit eco-friendly homes. The results indicated that a favorable attitude toward environmentally sensitive homes, high control in the ability to purchase sustainable homes, and the role of identification with green consumerism were statistically significant predictors of intention to inhabit such homes. However, social referents’ opinion relating to green and sustainable homes was not significantly related to the intention of inhabiting. The findings also indicated that owners of gated-guarded and detached dwellings, monthly household income and higher educational attainment were significantly related to the likelihood of residing in eco-friendly homes. Housing developers should have to take the lead to generate awareness of sustainability of green homes through education because increasing awareness creates demand for eco-friendly homes, which would in turn push house buyers to go green.